(untitled) (ART AND CULTURE BULLETIN, 2026)
This article analyzes current issues in improving the activitiyes of information resource centers in modern librariyes. The importance of implementing information technologiyes, improving service quality, and user-centered approaches will be highlighted. The main directions and prospects for the development of the library system are also outlined.